Somatosensory Psychophysical Losses in Inhabitants of Riverside Communities of the Tapajós River Basin, Amazon, Brazil: Exposure to Methylmercury Is Possibly Involved. - Eliana Dirce Torres Khoury; Givago da Silva Souza; Carlos Araújo da Costa; Amélia Ayako Kamogari de Araújo; Cláudia Simone Baltazar de Oliveira; Luiz Carlos de Lima Silveira; Maria da Conceição Nascimento Pinheiro (PLoS ONE, 2015)
The purpose of this work was to evaluate the somatosensory system of methylmercury-exposed inhabitants living in the communities of the Tapajós river basin by using psychophysical tests and to compare with measurements performed in inhabitants of the Tocantins river basin. We studied 108 subjects from Barreiras and São Luiz do Tapajós, two communities of the Tapajós river basin, State of Pará, Amazon, Brazil, aged 13-53 years old. Mercury analysis was performed in head hair samples weighting 0.1-0.2 g by using atomic absorption spectrometry. Three somatosensory psychophysical tests were performed: tactile sensation threshold, vibration sensation duration, and two-point discrimination. Semmes-Weinstein 20 monofilaments with different diameters were used to test the tactile sensation in the lower lip, right and left breasts, right and left index fingers, and right and left hallux. The threshold was the thinner monofilament perceived by the subject. Vibration sensation was investigated using a 128 Hz diapason applied to the sternum, right and left radial sides of the wrist, and right and left outer malleoli. Two trials were performed at each place. A stopwatch recorded the vibration sensation duration. The two-point discrimination test was performed using a two-point discriminator. Head hair mercury concentration was significantly higher in mercury-exposed inhabitants of Tapajós than in non-exposed inhabitants of Tocantins (p < 0.01). When all subjects were divided in two groups independently of age-mercury-exposed and non-exposed-the following results were found: tactile sensation thresholds in mercury-exposed subjects were higher than in non-exposed subjects at all body parts, except at the left chest; vibration sensation durations were shorter in mercury-exposed than in non-exposed subjects, at all locations except in the upper sternum; two-point discrimination thresholds were higher in mercury-exposed than in non-exposed subjects at all body parts. There was a weak linear correlation between tactile sensation threshold and mercury concentration in the head hair samples. No correlation was found for the other two measurements. Mercury-exposed subjects had impaired somatosensory function compared with non-exposed control subjects. Long-term mercury exposure of riverside communities in the Tapajós river basin is a possible but not a definitely proven cause for psychophysical somatosensory losses observed in their population. Additionally, the relatively simple psychophysical measures used in this work should be followed by more rigorous measures of the same population.